Ties that bind: Pentecostal churches, youth gangs, and the management of everyday life in the urban barrio - Thornton, Brendan Jamal (Religion, 2018)
In this article, I juxtapose Pentecostal churches with youth gangs, two popular barrio institutions that at first glance appear to be irreconcilable but when considered together evince organic parallels that reveal important insights into contemporary life in urban poverty. Reflecting on ethnographic data from the Dominican Republic and elsewhere, I argue that due to an analogous ritualization of everyday life - through rigorous rules and clearly defined consequences for breaking them - both Pentecostal churches and youth gangs, despite their ostensible differences, afford a unique kind of freedom in constraint, and by providing reliable spaces of predictability, control, and mastery, have become popular stages for managing the precariousness of barrio life in late modernity.